Co-operative learning as a tool in the teaching and learning of linear programming: A case of national curriculum vocational (NC(V)) level 3 multilingual students - Sipholi, K.; Machaba, F. M. (South African Journal of Higher Education, 2021)
This study explored how co-operative learning could be used in the teaching and learning of Linear Programming (LP) for NCV multilingual FET students. A qualitative case study was used in an FET college where students and their lecturers learn mathematics in a language that is not their first, main or home language. The data analysed showed that students had low language proficiency in the Language of Learning and Teaching (LoLT). This then calls for lecturers to apply different language practices, such as code-switching and co-operative learning, to enable students to understand the language in which tasks are presented. It is from understanding a task that students can employ different solution strategies to solve the problems presented to them. The data further revealed that code-switching and co-operative learning were practised as a teaching strategy to ensure an understanding of LP concepts in the lecturer’s classroom. Home language students were able to translate mathematical statements to symbolic form. Code-switching and discussions in their home languages further enabled them to understand the procedures and strategies of solving LP problems.